HAZARDS IDENTIFICATION AND RISK ANALYSIS IN POST PRINTING LABORATORIES OF STATE POLYTECHNIC OF CREATIVE MEDIA - Elviana Elviana; Antinah Latif; Dafa Algiasa Yudistira (Kreator, 2021)
Every workplace and activity has potential hazards and risks that can cause work accidents, as well as laboratories in the educational environment. Post-printing laboratories have the potential to have dangers and risks because of the sources of hazards and work activities by both students and instructur and operators. Theaims of this paper is to determine the potential hazards and risks; know risk assessment using HIRA method and control of hazards and risks. Data collection techniques used in this paper are observation, interviews and literature study. Based on the results of this paper, the potential hazard with the highest value is found in the type of activity operating a perfect binding machine with a total of 8 hazards. The risk assessment obtained a low risk level of 50%, extreme 30%, moderate 15% and high 5%. This extreme level of risk is influenced by the use of chemicals in the perfect binding process. Some controls have been implemented but some are not functioning properly. Suggested controls are engineering and administrative control design. Keywords: Hazard, Risk, HIRA method, Post printing